Using the FSB Key Attributes to Design Bank Resolution Frameworks for Non-FSB Members : Proportionality and Implementation Challenges - Nolte, Jan Philipp; Hoelscher, David (World Bank, Washington, DC, 2020)
This paper discusses how the Key Attributes could be implemented proportionally in non-FSB member jurisdictions in light of the structure and complexity of the banking sectors and the capacity of the authorities in those countries. The focus of this paper is on resolution regimes for banks, as banks are likely to be the main source of systemic risk in most non-FSB member countries.